1994
DOI: 10.1063/1.467202
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of vibronic population inversion with inclusion of molecular rotation

Abstract: This paper considers vibronic population inversion in the presence of molecular rotation. The objective is to invert the population of a vibronic level with populated rotational levels to a specific vibrational level in the excited electronic state regardless of the detailed population distribution in the final rotational levels. The control of the multilevel population inversion is achieved by design of a pump pulse through optimal control theory. The total energy fluence and the pulse peak intensity are impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Although the thermal averaging over the initial population of vibrational states contributes to the delocalization of the LIF signal, the disagreement between simulation and experiment remains substantial if rotation is omitted from the calculations. 10,11,75,76 In Fig. 6, we show the comparison of gas phase I 2 experimental measurements ͑solid line͒ with exact quantum simulations ͑dashed line͒ which now include rotation, for the same positive and negative chirped pair of pump pulses as in Fig.…”
Section: E Simulation and Experimental Results: Gas Phasementioning
confidence: 99%
See 2 more Smart Citations
“…Although the thermal averaging over the initial population of vibrational states contributes to the delocalization of the LIF signal, the disagreement between simulation and experiment remains substantial if rotation is omitted from the calculations. 10,11,75,76 In Fig. 6, we show the comparison of gas phase I 2 experimental measurements ͑solid line͒ with exact quantum simulations ͑dashed line͒ which now include rotation, for the same positive and negative chirped pair of pump pulses as in Fig.…”
Section: E Simulation and Experimental Results: Gas Phasementioning
confidence: 99%
“…In this figure, the theoretical results are in excellent agreement with the experimental measurements, confirming the importance of rotational motion in wavepacket dynamics. 10,11,75,76 More detailed analysis shows that there are two important rotational effects. The first is the decay of the anisotropic orientational distribution induced by the polarized pump pulse and then sampled by the polarized probe pulse.…”
Section: E Simulation and Experimental Results: Gas Phasementioning
confidence: 99%
See 1 more Smart Citation
“…In atoms [8] and in some spin systems (nuclear magnetic resonance), where two level approximations are reasonable, complete population inversion by pulses of electromagnetic radiation, where the entire population of one state is transferred to another state, is a long-established technique. The parallel solution for the electronic population of molecules, with their multiple rovibrational states, has not previously been found, although several theoretical calculations have been made [9][10][11][12]. In this Letter, we demonstrate that such a solution does exist for molecular systems and can be understood with simple physical models.…”
mentioning
confidence: 81%
“…Theoretical aspects of population inversion have been explored earlier along different lines. [20][21][22][23] Making use of displaced harmonic oscillator potentials, Somloi, Lorincz, and Rice 20,21 obtained the resonance condition for pulses much shorter than the time scale of vibrational motion and found that in this limit the displaced harmonic oscillator system responds to intense laser pulses as a two-level system. For relatively longer pulses, the concept of a pulse is not well defined and optimal control theory becomes the method of choice for maximizing population inversion.…”
Section: Introductionmentioning
confidence: 99%